2001
DOI: 10.1029/2000ja000262
|View full text |Cite
|
Sign up to set email alerts
|

Incoherent scatter radar identification of the dayside magnetic separatrix and measurement of magnetic reconnection

Abstract: Abstract. Incoherent scatter (IS) radar measurements of the ionospheric electron density are analyzed for the signature of the magnetic separatrix in the dayside ionosphere by comparison with separatrix locations determined using precipitating electron data from DMSP spacecraft within 1.5 hours in magnetic local time (MLT) of the Sondrestrom radar. A model of photoionization is used to remove its effects from the measured electron density to study the ionization by precipitating particles. The altitude of peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Other techniques for identifying the OCB include detection of the ionospheric electron density enhancement produced by precipitating trapped particles, for instance with an incoherent scatter radar (e.g. de la Beaujardiere et al, 1991;Blanchard et al, 2001), and identification of the spectral width boundary observed by coherent radars (e.g. Chisham and Freeman, 2003).…”
Section: Measuring the Open Flux Content Of The Magnetospherementioning
confidence: 99%
“…Other techniques for identifying the OCB include detection of the ionospheric electron density enhancement produced by precipitating trapped particles, for instance with an incoherent scatter radar (e.g. de la Beaujardiere et al, 1991;Blanchard et al, 2001), and identification of the spectral width boundary observed by coherent radars (e.g. Chisham and Freeman, 2003).…”
Section: Measuring the Open Flux Content Of The Magnetospherementioning
confidence: 99%
“…The dayside reconnection electric field has been measured extensively in this way under southward IMF conditions (Baker et al, 1997;Pinnock et al, 1999;Blanchard et al, 2001;Milan et al, 2003;Pinnock et al, 2003), but measurements under northward IMF conditions have been generally confined to determinations of the cross-polar cap potential from low-altitude spacecraft overflights or from model convection patterns (Cumnock et al, 1995;Weimer, 1995;Ruohoniemi and Greenwald, 1996). Cumnock et al (1995) measured a potential drop of ∼10-20 kV between the centres of the reverse convection cells during intervals of northward IMF.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this measurement is difficult, as it usually requires a conjunction of at least two observing instruments; one to determine the footprint of the X-line and a second to measure the plasma flow. Blanchard et al (2001) have shown how a single incoherent scatter radar can be used to measure the reconnection rate at a single meridian. Studies by Baker et al (1997) and Pinnock et al (1999) demonstrated the ability of the radars of the Super Dual Auroral Radar Network (SuperDARN) to perform the measurement, the greater field of view of a single Super-DARN radar extending the coverage to ∼2 h of MLT.…”
Section: Introductionmentioning
confidence: 99%